دور الشباب على مواقع التواصل الاجتماعي في تعزيز الهوية الوطنية - سميرة, ناصري (University of Eloued جامعة الوادي, 2020)
شهد العالم العربي خلال السنوات الماضية حراكا شبابيا واسعا من خلال ثورات التغيير ضد النظام ابتدأت بتونس ثم انتقلت إلى دول أخرى كمصر وليبيا، والباقي لم تحسم نتائجه وسوريا نموذج لهذا. أظهرت هذه الثورات ثقافة المجتمعات التي قادتها وخاصة فئة الشباب، من خلال طريقتهم في التعبير عن طريق استخدام مواقع التواصل الاجتماعية. أصبحت هذه المواقع مثل "الفيس بوك "،"تويتر" تعرف بالإعلام الاجتماعي الجديد، حيث تحولت من أداة إعلامية نصية مكتوبة إلى أداة إعلامية سمعية وبصرية تؤثر في قرارات المشتركين فيه وتحول الأقوال والأفكار إلى مشروعات عمل جاهزة للتنفيذ. فإن لها أيضا دورا في المناصرة و الضغط والتفاعل والتأثير، وفي تعزيزالهوية الوطنية إذا ما أحسن استثمارها واستغلالها وتوجيهها بشكل جيد. تعد مواقع التواصل الاجتماعي اليوم من المؤسسات المهمة التي تقوم بدور مهم في تربية وإكساب سلوكيات جديدة وأداة مهمة من أدوات التغيير في المجتمع حيث أن هذه المواقع كانت المحرك الأساسي للثورات والمظاهرات والأحداث التي شهدها العالم مؤخرا خاصة العربي. أضحى هذا العالم الرقمي الذي تلاشت عبره الحدود بأشكالها ليصبح العالم كله قرية افتراضية صغيرة بكل ما تحمله الكلمة من معنى، تنتقل الأفكار والقيم والثقافات فيه بسرعة الضوء من مكان إلى آخر دون حواجز أو قيود. ورغم دوره المهم في الحوار وتلاقح الثقافات، إلا انه لا يخلو أيضا من مخاطر قد تؤدي إلى فقدان الهوية بمختلف أبعادها سواء الدينية أو غيرها. During the past years, the Arab world have witnessed large movement of youth endeavoring through revolution to put in motion a regime change. It has started in Tunisia and spread to other countries such as Egypt and Libya. However, in other countries, as in Syria, the result is still inconclusive. Through their memes, trolls and social media expressions, those revolutions have demonstrated the socio-cultural traits of its pioneers, in general, and the young ones in particular. Social networks like Twitter and Facebook are recognized as the New Media which has been transformed from a written medium tool to an audio- visual one that affects the decisions of its adherents and embodies their words and thoughts into a ready-for-action projects. Moreover, this new social media plays significant advocacy, pressure and influence roles, and it also enhances that national identity of its adherents if it is used properly and efficiently. Nowadays, social media is considered as an important institution engaging in the business of raising and acquiring new set of behaviors and tools to bring about a change on society, as well as becoming the driving power behind protests, revolution and events around the world, and mainly in the Arab regions. More importantly, this digital world that has become a small virtual village, where boundaries and distances are meaningless, as well as the norms and values of culture are moving speedily everywhere, free of obstacles and constraints. However, despite its crucial role in establishing dialogues and acculturation, social network poses a risk of losing one’s religious and cultural identity or even worse.
مجلد11، عدد1
Keywords: وسائل التواصل؛ الشبكات العنكبوتية؛ الهوية الوطنية؛ األ من; Social Media, Networks, National Identity, Security